Comparing the degree of pelvic pain with the macroscopic features of endometriosis - Sonwani, Tarini; Biswas, Ratna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Endometriosis is considered as the chronic benign gynecologic disease which can cause chronic pelvic pain (CPP) and infertility. Endometriosis has affected almost 10% of the women of reproductive age. Methods: Thirty women diagnosed with endometriosis were studied. Pain intensity was assessed by visual analogue scale (VAS) and categorized as mild, moderate or severe accordingly. This was followed by laparoscopy/ laparotomy and staging of endometriosis which was done as per the American Society for Reproductive Medicine (ASRM) classification system. Corrective procedures were done simultaneously. Results: Mean age of women with endometriosis was 30±5.75 years. Majority had superficial implants (30%), 6.66% had deep implants and 6.66% had combination of superficial and deep implants. There was no significant difference between implants and severity of pain (p=0.069). There was a significant association between severity of pain with obliteration of POD. Significant association was seen between deeply infiltrating endometriosis (DIE) represented by the pouch of Douglas (POD) obliteration and severity of pain. Conclusions: Severity of pain was significantly associated with deeply infiltrating endometriosis (DIE) represented by the pouch of Douglas (POD) obliteration. However, no association was obtained between severities of pain with superficial implants.